2020
DOI: 10.1104/pp.20.00562
|View full text |Cite
|
Sign up to set email alerts
|

Genes of the RAV Family Control Heading Date and Carpel Development in Rice

Abstract: In plants, correct formation of reproductive organs is critical for successful seedset and perpetuation of the species. Plants have evolved different molecular mechanisms to coordinate flower and seed development at the proper time of the year. Among the plant-specific RELATED TO ABI3 AND VP1 (RAV) family of transcription factors, only TEMPRANILLO1 (TEM1) and TEM2 have been shown to affect reproductive development in Arabidopsis (Arabidopsis thaliana). They negatively regulate the floral transition through dir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 102 publications
2
28
0
Order By: Relevance
“…10 a-b). Previous studies suggested that the RELATED TO ABI3/VP1 ( RAV ) family members delay heading time by repressing Heading date 3a ( Hd3a ) and GIBBERELLIN 3-OXIDASE1/2 in rice ( Oryza sativa ) [ 49 ]. In the present study, we found that the quinoa RAV1 homolog ( AUR62035279 ) was regulated by 3 lncRNAs (2 positive lncRNAs, MSTRG.39390.2 , MSTRG.69967.1 ; 1 negative lncRNA: MSTRG.3121.1 ) (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…10 a-b). Previous studies suggested that the RELATED TO ABI3/VP1 ( RAV ) family members delay heading time by repressing Heading date 3a ( Hd3a ) and GIBBERELLIN 3-OXIDASE1/2 in rice ( Oryza sativa ) [ 49 ]. In the present study, we found that the quinoa RAV1 homolog ( AUR62035279 ) was regulated by 3 lncRNAs (2 positive lncRNAs, MSTRG.39390.2 , MSTRG.69967.1 ; 1 negative lncRNA: MSTRG.3121.1 ) (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Rice RAV transcription factors were phylogenetically clustered into four groups. Among these groups, most of the members in the red group contained both AP2 and B3 domains, and the members of the red group shared the same function in the flowering of both Arabidopsis and rice [ 11 , 12 ]. However, only 20% of the detected rice RAV genes contain introns.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the B3 domain, RAV family members TEM1 and TEM2 , which contain the AP2 domain, are negative regulators of flowering [ 11 ] by repressing the expression levels of FLOWERING LOCUS T ( FT ) and gibberellins [ 11 ]. Besides, Osnato et al first identified and named 12 RAV genes ( OsRAV1–OsRAV12 ) in rice and also found that OsRAV9 / OsTEM1 inhibits photoperiod flowering upstream of the flower activators OsMADS14 and Hd3a [ 12 ]. In addition, OsRAV11 and OsRAV12 , which act downstream of the flower homeotic factor, may have acquired a new function in carpel differentiation and seed size control [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…TEM1 and TEM2 repress trichome formation (Matías-Hernández et al, 2016), and floral transition under inductive and noninductive photoperiods (Castillejo and Pelaz, 2008;Osnato et al, 2012) as well as in response to low temperatures (Marín-González et al, 2015) and to plant age (Aguilar-Jaramillo et al, 2019). OsRAV9/OsTEM1 has a conserved function as a repressor of photoperiodic flowering upstream of the floral activators OsMADS14 and Hd3a in rice (Osnato et al, 2020).…”
Section: Introductionmentioning
confidence: 99%